Study of Diversity of Natural Dyes Plants in Egon Village Waigete District, Sikka Regency - Jovanti, Maria; Sada, Mariana; Moi, Maria Yasinta (Holistic Science, 2023)
This study aims to determine the types and organs of plants that are used as natural dyes for food, beverages, cosmetics and textiles used by the people of Egon Village, Waigete District, Sikka Regency. The method used is explorative method (roaming method). Determination of respondents using purposive and random methods. Determination of the types of natural coloring plants is done by describing the morphology of the plants, while their utilization is described based on the organ used. The results showed that the natural coloring plants found to be used in Egon Village consisted of 11 families of 13 plant species. The plant organs used are leaves (40%), fruit (20%), rhizomes 13%, roots, tubers, seeds each (7%), and stems 6%. The most dominant plant organ used is the leaf organ (40%)